Effect of remimazolam tosilate on early cognitive function in elderly patients undergoing upper gastrointestinal endoscopy. Issue 3 (3rd January 2022) - Tan, Yingjie; Ouyang, Wen; Tang, Yongzhong; Fang, Ning; Fang, Chao; Quan, Chengxuan
Abstract: Background and Aim: Remimazolam tosilate (RT) is under evaluation as a sedative for endoscopic procedures. Herein, we aimed to evaluate safety including cognition recovery of RT administered in elderly patients undergoing upper gastrointestinal endoscopy and assess its safety dosage. Methods: Ninety‐nine patients presenting for upper gastrointestinal endoscopy were randomized to receive 0.1 mg/kg RT (R1) or 0.2 mg/kg RT (R2), or propofol (P). Cognitive functions (memory, attention, and executive function) were measured via neuropsychological tests conducted before sedation and 5 min after recovery to full alertness. Adverse events were also assessed. Results: There were no statistical differences between postoperative and baseline results for R1 group and P group, whereas those for R2 group revealed worsened postoperative cognitive functions (immediate recall and short delay recall) than baseline ( P  < 0.05). Compared with P group, Scores demonstrated worse restoration of immediate recall in R1 group, immediate recall, short‐delayed recall, and attention function in R2 group ( P  < 0.05). Patients in R2 group had a longer sedation time (12.09 vs 8.27 vs 8.21 min; P  < 0.001) and recovery time (6.85 vs 3.82 vs 4.33 min; P  < 0.001) than that in R1 group and P group. Moreover, the incidence of hypotension was 3.0% in R1 group, whereas it was 21.2% in R2 group and 48.5% in P group ( P  < 0.05). Conclusion: The addition of 0.1 mg/kg RT as an adjunct to opiate sedation for upper gastrointestinal endoscopy not only achieves more stable perioperative hemodynamics but also achieves acceptable neuropsychiatric functions in elderly patients.